Object-oriented programming : a new programming paradigm / Syed Ahmad Aljunid and Nordin Abu Bakar (Universiti Teknologi MARA, Terengganu, 1992)
We begin by introducing a short history of types of programming languages. Object-oriented programming (OOP) is then discussed, stressing more on its revolutionary but yet evolutionary paradigm and approach. Its four main concepts namely encapsulation, data abstraction, inheritance, and polymorphism are discussed briefly. Lastly, we contend it is not only a viable and indispensable type of programming language but a new programming paradigm.